2022
DOI: 10.1002/ardp.202200326
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the development of celecoxib analogs as anticancer agents: A review

Abstract: Celecoxib is a nonsteroidal anti-inflammatory drug (NSAID) designed to be a selective cyclooxygenase-2 (COX-2) inhibitor. It was approved by the U.S. Food and Drug Administration for the treatment of inflammatory diseases such as osteoarthritis and rheumatoid arthritis. Additionally, celecoxib demonstrated potent antitumor and chemopreventive effects in vitro, in vivo, and in patients. The mechanism of celecoxib's chemopreventive effect is still not fully identified, but it is assumed to be multifactorial. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In 2022, Abdelhaleem et al [ 67 ] synthesized new celecoxib analogs and examined their anticancer effects on the MCF‐7 cell line. Celecoxib's trifluoromethyl group was replaced with the arylidene hydrazine‐1‐carbonyl moiety, which incorporated fluorine or methoxy groups.…”
Section: N‐acylhydrazones As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Abdelhaleem et al [ 67 ] synthesized new celecoxib analogs and examined their anticancer effects on the MCF‐7 cell line. Celecoxib's trifluoromethyl group was replaced with the arylidene hydrazine‐1‐carbonyl moiety, which incorporated fluorine or methoxy groups.…”
Section: N‐acylhydrazones As Anticancer Agentsmentioning
confidence: 99%
“…Particularly, the cytotoxic activities and selectivity were improved with the replacement of the electron-donating group with a chlorine group at the para-position of the phenyl ring. [66] In 2022, Abdelhaleem et al [67] synthesized new celecoxib analogs and examined their anticancer effects on the MCF-7 cell line. Celecoxib's trifluoromethyl group was replaced with the arylidene hydrazine-1-carbonyl moiety, which incorporated fluorine or methoxy groups.…”
Section: N-acylhydrazones As Apoptosis Inducersmentioning
confidence: 99%
“…The pyrazole ring is a privileged structural motif, which was widely found in many crucial compounds, such as drugs, active natural products, anti-tumor, antibacterial, and biological activities molecules. [1][2][3][4] In the top 200 small molecule pharmaceuticals by retail sales in 2020, many representative drugs such as Celecoxib, [5][6][7] Apixaban, 8 Ibrutinib, [9][10][11] and Ruxolitinib 12 have pyrazole structures (Figure 1). Due to the important effect of pyrazole scaffolds in pharmaceutical chemistry, exploring efficient method and mechanism to obtain pyrazole scaffolds is a preeminent goal to chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that celecoxib can regulate p21 and FAK molecules to block AKT activation, thus inhibiting the proliferation of tumor cells [11], and it can prevent the invasion and metastasis of cancer cells by mediating the PGE2/NF-kB pathway [12]. However, the FDA had withdrawn its approval for colon cancer in 2012 because celecoxib caused unaffordable adverse effects in patients and had a complex mechanism [13]. The application of celecoxib in cancer has only been studied with evidence-based medicine, and its complex multisystem adverse events (AEs) would affect its further therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Light on this, whether there is some correlation between its application and e cacy related to CNS has attracted the attention of this study. Furthermore, celecoxib is currently being explored in many cancer treatments with satisfactory results, whereas celecoxib was undone in its application by the FDA for colon cancer due to its terrible effects [13], We still must be wary of potential side effects behind their excellent e cacy. In conjunction with the results of the literature review, there is no research that has comprehensively reviewed and analyzed the detrimental reactions related to celecoxib.…”
Section: Introductionmentioning
confidence: 99%